2017
DOI: 10.18632/oncotarget.17417
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles of human foreskin fibroblast cells in response to orf virus

Abstract: Orf virus has been utilized as a safe and efficient viral vector against not only diverse infectious diseases, but also against tumors. However, the nature of the genes triggered by the vector in human cells is poorly characterized. Using RNA sequencing technology, we compared specific changes in the transcriptomic profiles in human foreskin fibroblast cells following infection by the orf virus. The results indicated that orf virus upregulates or downregulates expression of a variety of genes, including genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This ability to modulate viral infectivity provides powerful tools to study the fundamental mechanisms of arbovirus transmission and pathogenesis. In particular, the increased in vitro infectivity observed for the E1-V80A and V80I in HFF-1 cells, which have a competent innate immunity signaling pathway (Chen et al, 2017) is intriguing and suggests that this position can potentially be involved in regulatory processes other than fusion. Notably, this phenomenon of viral attenuation by position 80, is not exclusive to CHIKV, as we observed similar levels of attenuation in SINV, another member of the alphavirus genus.…”
Section: Discussionmentioning
confidence: 99%
“…This ability to modulate viral infectivity provides powerful tools to study the fundamental mechanisms of arbovirus transmission and pathogenesis. In particular, the increased in vitro infectivity observed for the E1-V80A and V80I in HFF-1 cells, which have a competent innate immunity signaling pathway (Chen et al, 2017) is intriguing and suggests that this position can potentially be involved in regulatory processes other than fusion. Notably, this phenomenon of viral attenuation by position 80, is not exclusive to CHIKV, as we observed similar levels of attenuation in SINV, another member of the alphavirus genus.…”
Section: Discussionmentioning
confidence: 99%
“…They found that multiple differentially expressed genes were enriched in GO terms such as immune response, inflammatory response and apoptosis, indicating that the host could defend virus invasion through immune response and induce cell apoptosis to block viral proliferation. Another study reported alterations of transcriptional profiles in human foreskin fibroblast cells following ORFV infection (Chen et al, 2017). A variety of genes involved in immune response, apoptosis, cell cycle, etc were differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…ORFV has a linear, double-stranded DNA genome approximately 130–140 kb in length and containing a putative 131 open reading frames (Delhon et al, 2004; Martins et al, 2017; Zhang et al, 2014a). To better understand the pathogenesis of ORFV, several previous studies have conducted genome sequencing of different ORFV isolates (Chi et al, 2015; Delhon et al, 2004; Zhao et al, 2010), as well as transcriptome sequencing of host cells following ORFV infection (Chen et al, 2017; Jia et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro infection with ORFV is usually performed in classical cell cultures using primary cells from sheep or ruminants for virus isolation and propagation. Regarding skin-derived primary keratinocytes or dermal fibroblasts, limited studies were undertaken with ORFV to evaluate cytopathic effects or transcriptomic profiles [11,12]. The infection of OTC generated from ovine foreskin primary lamb keratinocytes with ORFV resulted in ballooning degeneration of cells in the superficial layers [1].…”
Section: Introductionmentioning
confidence: 99%